2007
DOI: 10.1098/rsta.2007.2094
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous tissue: an excitable medium. A study using the retinal spreading depression as a tool

Abstract: According to its physicochemical properties, neuronal tissue, including the central nervous system (CNS) and thus the human brain, is an excitable medium, which consequently exhibits, among other things, self-organization, pattern formation and propagating waves. Furthermore, such systems can be controlled by weak external forces. The spreading depression (SD), a propagating wave of excitation-depression, is such an event, which is additionally linked to a variety of medically important situations, classical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Being an excitatory drug, nicotine indeed raises the excitability of the tissue for a short introduction period, which can be seen by the spontaneous wave being elicited when nicotine is perfused. The finding, that no continuous activity is induced, as has been found with other excitatory substances like the glutamate agonist quinoline-acid [14], is most probably due to the well known fast desensitisation of AChR´s [21,22] to which nicotine by definition binds. This also results in the prolongation of the latency after longer exposition to nicotine.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Being an excitatory drug, nicotine indeed raises the excitability of the tissue for a short introduction period, which can be seen by the spontaneous wave being elicited when nicotine is perfused. The finding, that no continuous activity is induced, as has been found with other excitatory substances like the glutamate agonist quinoline-acid [14], is most probably due to the well known fast desensitisation of AChR´s [21,22] to which nicotine by definition binds. This also results in the prolongation of the latency after longer exposition to nicotine.…”
Section: Discussionmentioning
confidence: 88%
“…As a consequence, especially in retinal tissue, a pronounced change in optical properties can be observed, the IOS concomitant with the retinal SD. Changes in parameters of this IOS induced by drugs can be used to describe the action of such substances [14].…”
Section: Introductionmentioning
confidence: 99%
“…The investigators surmised that the repetitive blindness episodes may have reflected waves of retinal spreading depression. Work by Hanke and Fernandes de Lima 8 has shown that retinal spreading depression spreads at a rate of 4 mm per minute and its duration in vitro is about 15 minutes. It has 2 peaks or phases known as the intrinsic optical signal.…”
Section: Discussionmentioning
confidence: 99%
“…48 Work by Hanke and de Lima has shown that retinal spreading depression spreads at a rate of 4 mm/minute and its duration in vitro is about 15 minutes. 49 Prophylactic aspirin, antiepileptic drugs, and tricyclic antidepressants have been reported to reduce the frequency of episodes of migraine with and without monocular visual defects. 47 Careful follow-up in retinal migraine patients is paramount because patients may manifest irreversible visual loss with their attacks, akin to migrainous infarction of the retina.…”
Section: Retinal Migrainementioning
confidence: 99%